INFLUENCE OF THE CROP YIELD PAIRING ABOVE- GROUND BIOMASS AND GRAIN CORN AND SOYBEAN - Јовановић, Маријана; Његован, Никола; Kрунић Невена (Economics of Agriculture, 2011)
By combining the potential of corn (maize) and legumes (soybean) using the appropriate spatial arrangement leads to increased yields above-ground biomass and grain. Maize exhibits dependence on the spatial distribution and types of hybrids, giving higher yields of crops growing in the joint. Soybean expresses the dependence of the spatial distribution and good results are obtained in pure sowing crops, so that’s paired extra maize crops. In this way reduces the amount of fertilizer utotrebljenog and the presence of weed species on arable land. This type of management combines elements of good agricultural practice with a high degree variety (biodiversity), while preserving natural resources, and obtaining agricultural products that meet customer needs.